2020
DOI: 10.1055/s-0040-1707155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functions of Oligomeric and Multidentate Dipyrrin Derivatives and their Complexes

Abstract: The dipyrrin–metal complexes and especially the boron complex 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) have recently attracted considerable attention because of their interesting properties and possible applications. We have developed two unique and useful ways to extend versatility and usefulness of the dipyrrin complexes. The first one is the linear and macrocyclic oligomerization of the BODIPY units. These arrangements of the B–F moieties of the oligomerized BODIPY units provide sophisticated fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 143 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…The BODIPY pigment and its derivatives are key entities for phototheranostics [1], including photodynamic therapy [2], functional optoelectronic materials [3], such as solar cells [4][5][6] and light emitting diodes [7], and stimuli-responsive materials [8][9][10][11]. In order to understand or predict the optical properties [12,13] of such important chromophore, and notably the lowest energy electronic transition, a very large number of investigations involving computational argumentations were reported but most of the time the correspondence between the calculated position and experimentally observed one turned out to be chronically poor, where differences ranging from 60 to 100 nm were commonly depicted [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The BODIPY pigment and its derivatives are key entities for phototheranostics [1], including photodynamic therapy [2], functional optoelectronic materials [3], such as solar cells [4][5][6] and light emitting diodes [7], and stimuli-responsive materials [8][9][10][11]. In order to understand or predict the optical properties [12,13] of such important chromophore, and notably the lowest energy electronic transition, a very large number of investigations involving computational argumentations were reported but most of the time the correspondence between the calculated position and experimentally observed one turned out to be chronically poor, where differences ranging from 60 to 100 nm were commonly depicted [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The longest maximum absorption wavelength (643 nm) of LSbCl 2 shifted to a longer wavelength compared to those of the related N 2 O 2 –dippyrin complexes of group 13 and 14 elements. 9,10 LSb(OH) 2 and LSbCl(OH) exhibited blue-shifted absorption compared with that of LSbCl 2 . Time dependent-density functional theory (TD-DFT) calculations revealed that the longest absorptions of these complexes could be attributed to their HOMO–LUMO transitions, and the frontier orbitals were distributed over the ligand π-systems.…”
mentioning
confidence: 96%
“…8 We utilised the N 2 O 2 -type dipyrrin ligands to synthesise complexes with group 13 (B, 9 Al, Ga, and In) and group 14 (Si, Ge, and Sn) elements (Fig. 1); 10 however, a zwitterionic dipyrrin VII was obtained instead of the P( iii )–dipyrrin complex. 11 Further, it is hypothesized that the complexation of N 2 O 2 -type dipyrrin ligands with heavier group 15 elements (As, Sb, and Bi) could yield air- and moisture-stable complexes.…”
mentioning
confidence: 99%